Antioxidant activity of Gryllus assimilis meal hydrolysed by Aspergillus oryzae proteases - Machado, J.; Porfírio, J. C.; Koike, M. A. [UNESP]; Fleuri, L. F. [UNESP]; Bagagli, M. P. (Brill Academic Publishers, 2022)
The consumption of insects is an alternative protein source of a high nutritional value, in comparison to other traditional animal and vegetable proteins, and is suitable for food and as animal feed. This work aimed to study the antioxidant activity of cricket meal (Gryllus assimilis) partially hydrolysed by proteases from a Aspergillus oryzae, which was cultivated in the cricket meal. The cricket meal showed great potential for obtaining protease from A. oryzae, with an average enzymatic activity of 112±8 U/g of dry substrate after 96 h of fermentation. The enzymatic extract applied to the cricket meal increased its antioxidant properties, increasing the reduction of the 2,2-diphenyl-1-picrylhydrazyl radical by 2 times, compared to non-hydrolysed cricket meal. These initial results are promising, demonstrating the benefits of the partial hydrolysis of cricket meal
Keywords: A. oryzae; Fermentation; Gryllus assimilis; Hydrolysis; Protease